Non-Alcoholic Steatohepatitis: A Review of Its Mechanism, Models and Medical Treatments - Peng, Cheng; Stewart, Alastair G.; Woodman, Owen L.; Ritchie, Rebecca H.; Qin, Cheng Xue (Frontiers in Pharmacology, 2020)
Non-alcoholic steatohepatitis (NASH) develops from non-alcoholic fatty liver disease (NAFLD). Currently, around 25% of the population is estimated to have NAFLD, and 25% of NAFLD patients are estimated to have NASH. NASH is typically characterized by liver steatosis inflammation, and fibrosis driven by metabolic disruptions such as obesity, diabetes, and dyslipidemia. NASH patients with significant fibrosis have increased risk of developing cirrhosis and liver failure. Currently, NASH is the second leading cause for liver transplant in the United States. More importantly, the risk of developing hepatocellular carcinoma from NASH has also been highlighted in recent studies. Patients may have NAFLD for years before progressing into NASH. Although the pathogenesis of NASH is not completely understood, the current “multiple-hits” hypothesis suggests that in addition to fat accumulation, elevated oxidative and ER stress may also drive liver inflammation and fibrosis. The development of clinically relevant animal models and pharmacological treatments for NASH have been hampered by the limited understanding of the disease mechanism and a lack of sensitive, non-invasive diagnostic tools. Currently, most pre-clinical animal models are divided into three main groups which includes: genetic models, diet-induced, and toxin+diet-induced animal models. Although dietary models mimic the natural course of NASH in humans, the models often only induce mild liver injury. Many genetic and toxin+diet-induced models rapidly induce the development of metabolic disruption and serious liver injury, but not without their own shortcomings. This review provides an overview of the “multiple-hits” hypothesis and an evaluation of the currently existing animal models of NASH. This review also provides an update on the available interventions for managing NASH as well as pharmacological agents that are currently undergoing clinical trials for the treatment of NASH.